Hearing the Living Word of God today? : a systematic-theological investigation into the authority and interpretation of scripture for contemporary Korean Presbyterianism - Yoon, Hyung-Chul (Stellenbosch : Stellenbosch University, 2011)
Thesis (DTh)--Stellenbosch University, 2011.